CHANGE OF REFLECTIVE CHARACTERISTICS OF ANISOTROPIC ENVIRONMENTS AT VARIATIONS OF PARAMETERS OF THE FILLER: LINEAR POLARIZATION - D. V. Gololobov; Ivanova; V. B. Kirilchuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Results of numerical analysis of the frequency dependences coefficient module the reflection of electromagnetic waves with linear polarizations of the electrodynamics parameters of anisotropic medium plasma of this kind. A comparison of these curves for an isotropic and anisotropic fillers. The regularities transformations for fixed frequencies characteristics of the electrodynamics parameters of a stream of particles that penetrate а magnet the dielectric filler. Foregoing results can be the basis for the creation of radio systems for the detection and identification of anisotropic heterogeneities on the background underlying isotropic medium.